ALIH KODE DAN CAMPUR KODE PADA SAAT PEMBELAJARAN DI KELAS VIII SMP NEGERI 3 PANGURURAN - Rani Fricyla; Syahfitri, Dian; Arianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the forms of code-switching and code-mixing of the Batak language and the factors influencing their use in the process of Indonesian language learning in Grade VIII at SMP Negeri 3 Pangururan. Language as a means of social communication demonstrates complex dynamics in bilingual communities such as those in Samosir Regency. In the classroom context, teachers and students frequently switch and mix Indonesian with Batak during instructional interactions. This study employed a descriptive qualitative method. The data were collected through observation of classroom interactions. The findings indicate that code-switching and code-mixing of the Batak language commonly occur during Indonesian language instruction. These phenomena are influenced by speakers’ language habits, limited Indonesian vocabulary, and interlocutor-related factors. This study offers novelty in terms of research location, participants, and learning context, and is expected to contribute to language learning practices and sociolinguistic studies, particularly concerning code-switching and code-mixing.